2016
DOI: 10.1097/hjh.0000000000000928
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for restenosis, and its impact on blood pressure control after percutaneous transluminal renal angioplasty in hypertensive patients with renal artery stenosis

Abstract: The frequency of restenosis after renal PTA is significant, and the presence of restenosis diminishes the benefit of its treatment, especially for FMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
0
19
0
3
Order By: Relevance
“…At 5.1-year mean follow-up of these patients, 56 patients (32%) developed restenosis (14). In the patients with atherosclerotic RAS (70% of the group) in this study, no significant reduction in systolic blood pressure was found (14).…”
mentioning
confidence: 48%
See 2 more Smart Citations
“…At 5.1-year mean follow-up of these patients, 56 patients (32%) developed restenosis (14). In the patients with atherosclerotic RAS (70% of the group) in this study, no significant reduction in systolic blood pressure was found (14).…”
mentioning
confidence: 48%
“…At 1-year mean follow-up of 175 patients with hypertension due to RAS treated with percutaneous transluminal renal angioplasty (PTRA), 35 patients (20%) also developed restenosis (14). At 5.1-year mean follow-up of these patients, 56 patients (32%) developed restenosis (14). In the patients with atherosclerotic RAS (70% of the group) in this study, no significant reduction in systolic blood pressure was found (14).…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…In atherosclerotic renal stenosis, a history of cardiovascular disease (hazard ratio (HR) 2.84) and a 90% or greater stenosis (HR 3.95) are independent predictors of restenosis. 33 Fibromuscular dysplasia is also an independent factor of restenosis after endovascular angioplasty (HR 2.65). In these patients, primary and assisted primary patency is 95%, 71% and 50%, and 100%, 100% and 100% at 1, 5 and 9 years, respectively.…”
Section: Renal Artery Disease Mid and Long-term Outcomementioning
confidence: 99%
“…Furthermore, the long-term result of PTA is limited by the unwelcome occurrence of recurrent stenosis (RS) that may additionally impact the final effect of PTA. The RS rate following RAS procedures is estimated at 6-40% [5][6][7][8]11]. However, the determinants of RS are poorly established.…”
Section: Introductionmentioning
confidence: 99%